Reductions to main meal portion sizes reduce daily energy intake regardless of perceived normality of portion size: A 5 day cross-over laboratory experiment - Haynes, A; Hardman, CA; Halford, JCG; Jebb, SA; Mead, BR; Robinson, E (BioMed Central, 2020)
Background: Smaller portions may help to reduce energy intake. However, there may be a limit to the magnitude of the portion size reduction that can be made before consumers respond by increasing intake of other food immediately or at later meals. We tested the theoretical prediction that reductions to portion size would result in a significant reduction to daily energy intake when the resulting portion was visually perceived as ‘normal’ in size, but that a reduction resulting in a ‘smaller than normal’ portion size would cause immediate or later additional eating.